Nível sérico de infliximabe no tratamento de crianças e adolescentes com doença de Crohn e colite ulcerativa - Komati, Juliana Tiemi Saito [UNIFESP] (2019)
Objective: The objective of the study was to compare the Quantum Blue® Infliximab rapid test to ELISA RIDASCREEN® IFX Monitoring test in inflammatory bowel disease pediatric patients and the validation of Quantum Blue® Infliximab rapid test. Methods: The study was conducted at the Pediatric Gastroenterology Clinic of Federal University of São Paulo, in pediatric patients with Crohn's disease and ulcerative colitis who received infliximab maintenance treatment. Firstly, the samples were analyzed through Quantum Blue® Infliximab rapid test and then sent and analyzed by ELISA RIDASCREEN® IFX Monitoring assay and Quantum Blue® Infliximab, in Switzerland. Results: The mean age of patients was 13,7 ± 4,1 years; 51,7% masculine gender; 89,7% with Crohn´s disease and 10,3% with ulcerative colitis. Trough levels measured by Quantum Blue® Infliximab in Fleury and Switzerland had good reproducibility, with intraclass correlation coefficient = 0,81. There was a positive linear correlation (p < 0,001) between Quantum Blue® Infliximab Fleury and Switzerland and between ELISA RIDASCREEN® IFX Monitoring and both Quantum Blue® Infliximab, with Pearson’s correlation analysis. Conclusions: Quantum Blue® Infliximab test and ELISA RIDASCREEN® IFX Monitoring assay are comparable. The rapid test provides infliximab trough level in 15 minutes with accuracy, is user friendliness, and allows the dose adjustment in the next medication infusion.